Repression of oxidative phosphorylation sensitizes leukemia cell lines to cytarabine. Issue 6 (3rd July 2018) - Yucel, Burcu; Sonmez, Mehmet
ABSTRACT: Objectives: Leukemia is a group of bone marrow cancers and drug resistance is one of the challenges in treatment. Caffeic acid phenethyl ester's (CAPE's) anti-proliferative and apoptotic properties have been reported in leukemia cell lines. However, CAPE's effect on drug resistance and cellular metabolism is still unknown. Thus, in this study, we aimed to explore CAPE's effect on drug resistance and oxidative phosphorylation (oxphos). Methods: Leukemia cell lines NB-4, HL-60, and K562 were treated with CAPE. ATP-based cell viability assay was used. For gene expression studies, RNAs were isolated and reverse transcribed. To investigate CAPE's effect on mitochondrial dysfunction in AML cell lines, we examined oxygen consumption rates (OCRs) in our cell lines. Results: We found 5 μM CAPE sensitized all cell lines to cytarabine. This similar effect was also observed in the Decitabine-resistant K562 cell line. However, no difference was seen in MDR1 expression upon CAPE treatment in all cell lines. OCR significantly decreased upon CAPE treatment in all cell lines, while the expression of key regulatory glycolytic enzymes increased in K562 and NB-4 cell lines. Expression of STAT3 also changed upon CAPE treatment. Discussion: Our results suggested that CAPE alters cellular metabolism by decreasing oxphos and increasing glycolysis in K562 and NB-4 cells. Furthermore, CAPE treatment altered STAT3 expression regarding alterations in oxphos and aerobic glycolysis. Conclusion: Our results suggest a new property of CAPE, which is oxphos repression, and a presumptive link between altered metabolism and drug resistance.